Indonesian Students’ Perception on Communication Language and Cultural Study in International Credit Transfer Program - Alimuddin, Supardi Bin; Rahman, Ali Wira; Nasrullah, Nasrullah (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2023)
This research was conducted to obtain the Indonesian Students’ Perception on Communication Language in the International Credit Transfer Program. This research also conducted to obtain the Cultural Study in the International Credit Transfer Program based on the students’ perception. This research used Qualitative Descriptive by design conducted with students. The population of this research is the students of English Department of Muhammadiyah University of Parepare who have joined the International Credit Transfer Program in Tarlac Agriculture University in Phillipines. The respondents of this research consist of three respondents. In addition, the researcher conducted interview and questionnaire to obtain the data. The result of this research showed that the students’ have some various perception of this program that discussed about communication language and cultural study based on the result of interview and questionnaire. English language is the efficient tool of communication in this program based on the result of questionnaire. It is because English the international language that used to unity all people in this world in communication language. Besides, the result of this research also showed that students’ perception toward the importance of cultural study that discuss about the culture, traditions, habits, dialect and learning method. It is because, it can help the students to make a differences between foreign culture and our local culture to make them proud with our culture and plays an important role in learning process for students themselves.